Pengaruh Kelengkapan Fitur, Kemudahan Transaksi dan Keamanan Aplikasi terhadap Kepuasan Nasabah Byond By BSI Di Era Transformasi Digital - Jannah, Dea Miftahul; Bayumi, Muhammad Rahman; Lemiyana, Lemiyana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to analyze the influence of feature completeness, ease of transactions, and application security on Byond By BSI customer satisfaction in the era of digital transformation. This study used a quantitative approach with a purposive sampling technique. The sample consisted of 100 respondents, who were customers of Bank Syariah Indonesia at the Palembang Demang branch, ranging in age from teenagers to productive age. Data were collected through distributed questionnaires using paper questionnaires and distributed Google Form links.The results showed that feature completeness had a significant and positive direct effect on customer satisfaction. Conversely, ease of transactions had a significant and positive effect on customer satisfaction, and application security also had a significant and positive effect on customer satisfaction. The third variable, namely feature completeness, ease of transactions, and application security, had a positive and significant effect on Byond By BSI customer satisfaction in the era of digital transformation.